2011
DOI: 10.1029/2010gc003481
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic sensitivity of paleoenvironmental proxies: A rock magnetic study of Australian continental margin sediments

Abstract: [1] A rock magnetic study of the upper 40 m of the Ocean Drilling Program Site 133-820A recovered at the outer edge of the northeastern Australian continental margin shows that downcore variations in magnetic parameters are diagenetically driven and correlate with the changes in global sea level. We identified intervals enriched in single-domain (SD) magnetite in the studied section. Unlike previous studies that postulated a detrital source, we show that the bulk of the SD fraction is biologically produced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 94 publications
3
43
1
Order By: Relevance
“…These results contrast with the reactivity of iron-bearing minerals to sulfide, where magnetite has a similar reactivity to goethite and hematite (Poulton et al, 2004). It also contrasts with other studies in which goethite has been reported to be more sensitive to reductive dissolution than hematite (Abrajevitch and Kodama, 2011). This discrepancy can be explained by the grain size of different magnetic minerals in Eastern Mediterranean marine sediments.…”
Section: Diagenetic Imprint On Magnetic Mineralscontrasting
confidence: 55%
See 1 more Smart Citation
“…These results contrast with the reactivity of iron-bearing minerals to sulfide, where magnetite has a similar reactivity to goethite and hematite (Poulton et al, 2004). It also contrasts with other studies in which goethite has been reported to be more sensitive to reductive dissolution than hematite (Abrajevitch and Kodama, 2011). This discrepancy can be explained by the grain size of different magnetic minerals in Eastern Mediterranean marine sediments.…”
Section: Diagenetic Imprint On Magnetic Mineralscontrasting
confidence: 55%
“…Once deposited in sediments, the signal of airborne magnetic minerals can be overprinted by other detrital or biogenic sources (e.g., Hesse, 1994;Roberts et al, 2011). Moreover, loss of detrital magnetic minerals or authigenic growth of new magnetic phases can occur during sedimentary diagenesis (Hounslow and Maher, 1999;Abrajevitch and Kodama, 2011;Liu et al, 2012a;Roberts, 2015, submitted). Adequate evaluation of the reliability of magnetic minerals as recorders of eolian dust deposition, therefore, demands careful, case-specific investigation of the processes that drive the formation, transportation, accumulation and preservation of magnetic minerals in sediments (Maher, 2011;Liu et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are increasingly undertaken to characterize changes in contributions to the total remanent magnetization and in magnetic grain size of sedimentary archives of various origins from past and present continents and oceans (e.g., Abrajevitch and Kodama, 2011;Lascu et al, 2012;Chen et al, 2014;Nie et al, 2014;Hyland et al, 2015;Fabian et al, 2016;Maxbauer et al, 2016c;Zhang et al, 2016). However, obtaining mineral compositions of an ensemble of components via these methods is only possible indirectly through a series of assumptions or a priori knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of biomagnetite is also observed in the low-MS interval, but its origin still needs to be confi rmed in the future. Variations in detrital titanomagnetite content at Bidart can be explained by several causes, such as (1) a rapid sea-level rise (e.g., dilution and remoteness to the source), (2) diagenetic reduction (Abrajevitch and Kodama, 2011), or (3) annihilation of iron oxides at or close to their continental source. The third hypothesis is tested here as a consequence of the huge Deccan volcanic gas emissions and resulting acid rains, which could have dissolved the continental magnetite grains before any riverine transfer to the oceanic basin.…”
Section: Low-ms Interval: Consequence Of Deccan Phase 2 Acid Rains?mentioning
confidence: 99%